Important Letters - Planning Commission (Planning Commission, 1964)
Multi-purpose project is sanctioned for execution, a reasonably good over all report and estimate for the whole project should be prepared. The project will generally consist of the following: (1) Dam and its appurtenant works. (2) Hydro-electric power plant. (3) Canal irrigation system. (4) Power line transmission. (1) and (3) form the irrigation part (almost entirely of civil engineering works). (2) and (4) consist partly of Civil Engineering and partly of electrical engineering works. Reference is made in this note to the Civil Engineering works of the project. (2) The estimates for the dam will be generally prepared after collecting the following data : Dam line surveys of the dam site finally selected, foundation explorations to get general data of the nature and levels of rock, reservoir bed surveys, levels and location surveys of various component works such as housing schemes for construction personnel, access roads and bridges, construction material with quantity surveys. Based on the above, designs for the dam in earth and masonry sections will be made out, and an estimate with quantities and rates prepared. This estimate will contain a fair amount of detail for the major components like the dam; but for the minor works, such as buildings, roads, water supply and drainage works, lump sum provisions will be made but each such unit will as far as possible be detailed, lump sums provided being based on the judgment and experience of the Engineer preparing the project report and estimate.
Various Matters Concerning Irrigation and Power Issued from the Planning Commission to the State Governments, Etc.